Gender Differences in Farmers’ Communication Pattern of Subang Regency - Ferdi Fathurohman; Nurul Mukminah; Rita Purwasih (Politeknik Negeri Bali, 2019)
Model of communication in agricultural communication practices in Indonesia particularly in Subang Regency has developed parallel to the concept of development communication and community development. This research aims to analyze the difference of communication pattern Member farmer groups against business success based on gender. The sample in this study amounted to 90 people from 18 farmers groups in Kabupaten Subang. The data collected through the survey with a questionnaire and Focus Group Discussion (FGD). The analysis of the test used was different from independent samples t-tests to test hypotheses posed. The study found that there were no significant differences based on gender-related patterns of communication that affect the success of the farmer. These findings indicate that gender is not a guarantee of a person's been doing better communication pattern.